P114 STING. Steroid Injections DurinG Covid-19. A cross speciality call. (8th April 2021) - Hardman, Lotte; Elamin, Salma; Giddins, Grey; Gardiner, Matthew; Reay, Emma; Hardman, Lotte
Abstract: Introduction: An important clinical question during the Covid -19 pandemic is the safety of steroid use. Guidelines published by rheumatology, physiotherapy, orthopaedic and pain medicine societies have advised on the restricted use of corticosteroids for musculoskeletal and rheumatic conditions. For clinicians across the specialities there is a challenge to safely conducting best practice, yet ensuring patients have access to the significant functional benefits of steroid injections. Methods: The STING prospective service evaluation will collect data on steroid injections undertaken during this part of the pandemic. Clinicians will be able to input information on patient demographics, background Covid risk and steroid injection specifics. At follow up at 4-6 weeks complications and Covid specific outcomes will be recorded, as well as patient perceived symptom improvement. Each unit collecting data will have assigned collaborator(s), with a senior consultant validating the data. Data will be collected and managed using Research Electronic Data Capture (REDCap). Data collection and management will adhere to Caldicott II principles and GDPR. Results: Results will be analysed through RedCap and compared to national Covid incidence. Local complication and patient reported outcomes will be compared between specialities, environments and steroid specifics (volume, location etc.). Conclusion: A pan-speciality look at steroid injection use during the pandemic will be useful primarily to contribute to understanding the safety of steroid use. Secondarily to look at cross speciality differences in administration, PROMs and to appreciate patient groups who may be excluded from steroid treatment. Join the team! Head to RSTN to get involved.